EFFECTIVENESS OF GUIDED IMAGINATION THERAPY USING THE BARCODE WEBSITE APPLICATION (IMAJICARE) ON PAIN SCALES IN POST OPERATIVE APPENDECTOMY PATIENTS AT THE CILEGON CITY GENERAL HOSPITAL - Leili Dewi Rahmadani; Siti Wasliyah (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Post appendictomy pain is a common problem that requires effective treatment. Guided imagery therapy is a promising non-pharmacological method, but its manual implementation has not been optimized. This study evaluates the effectiveness of the barcode website based ImajiCare application to reduce post-appendicectomy pain. This study aims to determine the effectiveness of using guided imagination therapy based on a barcode website application ImajiCare on the pain scale in patients post appendicectomy surgery at Cilegon City Hospital. This study used a quantitative design with the Quasy Experimental method and a two group pre test post test design. The sample consisted of 36 respondents who were divided into two groups, namely 18 intervention group respondents who used the ImajiCare application and 18 control group respondents who received manual imagination therapy selected by purposive sampling. Pain scale measurements were made using the Numeric Rating Scale (NRS) before and after the intervention, and the data were analyzed using the Wilcoxon test. The intervention group experienced a decrease in the average pain score from 5.39 to 1.83. The control group experienced a decrease from 5.44 to 2.28. Both methods were effective in reducing pain (p-value 0.000). Although ImajiCare showed a slightly greater reduction, the difference in effectiveness between the two groups was not statistically significant (p-value 0.172). ImajiCare and manual guided imagery therapy are both effective in reducing post appendicectomy pain. Imajicare offers the advantages of patient independence and efficiency, although its effectiveness is not significantly better than manual therapy.